2016
DOI: 10.5144/0256-4947.2016.165
|View full text |Cite
|
Sign up to set email alerts
|

Balloon kyphoplasty or percutaneous vertebroplasty for osteoporotic vertebral compression fracture? An updated systematic review and meta-analysis

Abstract: BACKGROUNDBoth kyphoplasty (KP) and vertebroplasty (VP) are effective for patients with osteoporotic vertebral compression fracture (OVCF), but which approach might be more effective remains unclear, so we decided to update earlier systematic reviews.OBJECTIVEReview and analyze studies published as of August 2015 that compared clinical outcomes and complications of KP versus VP.DESIGNSystematic review and meta-analysis.SEARCH METHODPublished reports up to August 2015 were found in PubMed, EMBASE and the Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 51 publications
0
43
1
Order By: Relevance
“…6 The second most recent review 24 identified two randomized trials. The study conducted by Bae et al 25 27 reviewed not only primary studies, but systematic reviews as well.…”
Section: Data Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 The second most recent review 24 identified two randomized trials. The study conducted by Bae et al 25 27 reviewed not only primary studies, but systematic reviews as well.…”
Section: Data Extractionmentioning
confidence: 99%
“…The latest review was published in 2016, 6 and included 4 randomized trials, 14 prospective cohort studies, and 14 retrospective cohort studies for analysis. 6 The second most recent review 24 identified two randomized trials.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations